Pengaruh Job Insecurity dan Work Stress Terhadap Turnover Intention dengan Job Satisfaction Sebagai Variabel Mediasi: Studi pada Karyawan Kantor PT. Semarang Garment - Della Evitriana; Christantius Dwiatmadja (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Turnover Intention is a person's desire to leave their current job to get a better job than their previous workplace High turnover rate can result in problems for the company. The purpose of this study is to determine the effect of Job Insecurity and Work Stress on Turnover Intention with Job Satisfaction as a Mediation Variable at PT Garment Semarang. This study was conducted at PT Garment Semarang, with a sample taken as many as 50 people using the saturated sample method, where this saturated sample method used the entire population as respondents in the study. Data collection was carried out by distributing questionnaires using a Likert scale. The results of the study show that there is a positive influence of job insecurity on turnover intention. There is a positive influence of work stress on turnover intention There is a negative influence on job insecurity on job satisfaction. There is an influence of work stress on job satisfaction. There is an influence of job satisfaction on turnover intention. There is an effect of job insecurity on turnover intention mediated by job satisfaction. There is an effect of work stress on turnover intention mediated by job satisfaction. . Employees who have feelings of insecurity at their jobs and feel high work stress do not directly have the intention to leave the company. This is because one of the most important factors that affect the decision is work performance. This study is expected to be a reference and supporting evidence regarding the influence of each variable discussed in this study. Keywords: Job Insecurity; Work Stress ; Turnover Intention; Job Satisfaction